Facilitating Professional Growth and Autonomy Development of In-Service English Teachers through a Blog: A Case Study in Iran - Anoosheh, Behroozi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In order to help teachers maintain their professionalism and empower them to keep up with the indispensable changes inherent to their career, it is crucial to facilitate teachers’ professional development. Professional development initiatives are believed to be more efficient if they are specifically designed and implemented to accommodate needs, lacks, and challenges of the teachers in a certain context. Established on these considerations and through incorporating the theoretical bases of constructivism and cognitive apprenticeship, this research aims to investigate the perceptions of the participating teachers about a professional development initiative which was mediated through a blog addressing the concepts of learner autonomy and learner-centeredness and further explore the participating teachers’ perceptions towards their professional growth and autonomy. To this end, data was collected through three questionnaires, two interviews, and blog entries from four Iranian teachers of English, who were interested in developing their knowledge and practice of teaching along with the principles of learner autonomy and learner-centeredness. The design of the study was qualitative-dominant and based on the principles of multiple-case studies. Following the principles of deductive thematic analysis, this research adopted Evan’s (2014) professional development model which identifies eleven dimensions of change categorized under three primary developmental components as behavioral, attitudinal, and intellectual. The model suggests that change often occurs across more than one component. However, for professional development to occur, it does not require change to take place in every single dimension. According to Evans (2014), professional development is multi-dimensional which comes about through a chain of reactions at micro-level; that is, one change would lead to another, which subsequently makes a cycle of chain-reaction episodes. Analysis of the data revealed that the offered professional development initiative worked efficiently to foster professional growth of the participating teachers with regard to the concepts of learner autonomy and learner-centeredness. Moreover, the participating teachers believed that their perceived professional growth positively contributed to their autonomy development.

ÖZ: Öğretmenlerin mesleklerini sürdürmelerine yardımcı olmak ve kariyerlerinin doğasında bulunan değişikliklere ayak uydurmalarında onları güçlendirmek için, öğretmenlerin mesleki gelişimine destek sağlamak çok önemlidir. Mesleki gelişimi amaçlayan girişimler, belirli bir bağlamda öğretmenlerin mesleki ihtiyaçlarını, eksikliklerini ve zorluklarını karşılamak için özel olarak tasarlanır ve uygulanırsa daha verimli olacaktır. Bu düşünceleri temel alan ve yapılandırmacılık ve bilişsel çıraklık teorilerinin prensipleri üzerine kurgulanan bu araştırma, katılımcı öğretmenlerin, öğrenen özerkliği ve öğrenci merkezli dil öğretimi kavramlarını ele alan ve bir blog üzerinden yürütülen bir mesleki gelişim girişimi hakkındaki algılarını araştırmayı ve buna ek olarak, katılımcı öğretmenlerin mesleki gelişimlerine ve özerkliklerine yönelik algılarını keşfetmeyi amaçlamaktadır. Bu amaçla, ‘öğrenen özerkliği’ ve ‘öğrenci merkezlilik’ ilkeleri konusunda öğretim bilgilerini ve uygulamalarını geliştirmek isteyen dört İranlı İngilizce öğretmeninden üç anket, iki mülakat ve blog ortamında paylaştıkları yazışmalardan oluşan veri toplandı. Çalışma ağırlıklı olarak nitel araştırma özelliği taşımasının yanı sıra çoklu durum çalışma ilkelerine dayanmaktadır. Tümdengelimli tematik analiz ilkelerini izleyen bu araştırmada, Evans’ın (2014) davranışsal, tutumsal ve zihinsel olmak üzere üç temel gelişim bileşeni altında kategorize edilen on bir değişim boyutunu tanımlayan mesleki gelişim modeli kullanılmıştır. Model, değişimin genellikle birden fazla bileşende gerçekleştiğini, ama mesleki gelişimin oluşması için her boyutta değişiklik olmasının gerekmediğini öngörmektedir. Evans'a (2014) göre mesleki gelişim, mikro düzeyde reaksiyonlar zinciri yoluyla ortaya çıkan çok boyutlu bir olgudur; yani, bir değişiklik diğerine yol açar ve bu da daha sonra bir zincirleme reaksiyon dönemi döngüsü oluşturur. Verilerin analizi, sunulan mesleki gelişim girişiminin, katılımcı öğretmenlerin ‘öğrenen özerkliği’ ve ‘öğrenci merkezli’ öğretim kavramlarına ilişkin mesleki gelişimlerine katkı koyduğunu ortaya koymuştur. Ayrıca, katılımcı öğretmenler algıladıkları mesleki gelişimlerinin özerklik gelişimlerine olumlu katkıda bulunduğunu ifade etmişlerdir.
Doctor of Philosophy in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2021. Supervisor: Prof. Dr. Ülker Vancı Osam
Keywords: English Language Teaching (ELT) Department; English Language--Study and Teaching